Fluorescence based characterization of early oral squamous cell carcinoma using the Visually Enhanced Light Scope technique. Issue 9 (September 2017) - Burian, Egon; Schulz, Caterina; Probst, Florian; Palla, Benjamin; Tröltzsch, Matthias; Maglitto, Fabio; Califano, Luigi; Ehrenfeld, Michael; Otto, Sven
Abstract: Objectives: Several diagnostic tools have been developed to assess benign and potentially malignant disorders of soft tissues. In this study, we aimed to assess the value of the VELscope ® (Visually Enhanced Light Scope) imaging device as a technical tool to investigate malignant lesions of the oral cavity. Material and methods: In this retrospective study we analyzed the photographs of 90 patients who suffered from malignant oral soft tissue lesions or carcinoma in situ (CIS) from 2008 to 2014 in the Clinic of Oral and Maxillofacial Surgery of LMU in Munich. Results: In 85.6% of the cases fluorescence quenching/loss could be detected. The average value for the colour red shows a significant difference in pathologic and physiologic tissues (p = 0.007) with a higher median for pathologic tissues. For the colours green and blue our measurements show significantly higher values in the healthy tissue (p < 0.001.). The shade of red showed significantly higher values for pathologic tissues when compared to all three colours (p < 0.001). Furthermore, the shades of green and blue showed significantly lower values in the pathologic tissue (p < 0.001). Conclusion: In the near future, VELscope ® could help to a greater extent than visual observation alone in identifying the margins of tumor resections. VELscope ® still lacks the ability to identify the overall risk level of oral lesions. Highlights: Under VELscope ® exposure normal tissue fluoresces light green. Dysplastic changes of epithelium cause loss of physiologic autofluorescence. We try to determine the reliability of fluorescence loss in histologically proven OSCC. Our results show a significant difference between neoplastic and physiologic mucosa. VELscope ® may be a beneficial tool in the evaluation of mucosal lesions.